Postpartum Deterioration of Hemodynamics in a Case of Uncorrected Ebstein's Anomaly - Masato Kimura; Shuhei Kakizaki; Seiichi Tazawa; Osamu Adachi; Yoshikatsu Saiki; Shigeo Kure (Case Reports in Cardiology)
Ebstein's anomaly is a rare congenital cardiac malformation that is characterized by abnormalities of the tricuspid valve and right ventricle. Pregnancy is usually well tolerated unless cyanosis or arrhythmia develops. We report a case with Ebstein's anomaly, whose condition was asymptomatic before pregnancy but remarkably deteriorated down during the postpartum period, even though a successful pregnancy and cardiac surgery were achieved. Women with Ebstein's anomaly should be carefully assessed and may need to be advised to have corrective surgery prior to pregnancy even if they were asymptomatic.